Organizational factors related to attracting job seekers higher in hardiness. (10th May 2019) - Eschleman, Kevin J.; Mast, David; Coppler, Quentin; Nelson, Jerrod
Abstract: Building an organization of workers who thrive in demanding environments begins with recruitment of workers with personality traits predictive of resilience. We integrate fit theories to determine how job advertisement information may attract job seekers higher in psychological hardiness (sense of control, feelings of commitment to many things in life, perceptions of challenge). Across two studies, we manipulated hypothetical job advertisements that were presented to current workers seeking new employment. Job seekers higher in hardiness were more attracted to working with hardy coworkers, less attracted to coping resources, and more attracted to high emotional labor demands compared to job seekers lower in hardiness. A discussion for how organizations may craft job advertisement content to improve their recruitment efforts is provided.